Carboxylic acid modulated in situ growth of Zr-based MOFs on carboxylated cotton fabrics for removal of Cr(VI) from aqueous solutions - Xie, Jinshan (2024)
In this paper, carboxylated cotton fabric (CF-Ph-COOH) were obtained as active substrate by diazonium radical polymerization modification of cotton fibers. Then the MOF fabric composites were prepared by in situ growth of metal zirconium ions (Zr) and organic ligands on the surface of carboxylated cotton fabrics under carboxylic acid modifier. MOF fabric composites with controllable morphologies structures were achieved by regulating organic ligands, reaction time the type and dosage of regulator (formic acid and acetic acid). The prepared acetic acid regulated MOF fabric composites were designated as CF-HAc1-UiO-66, CF-HAc2-UiO-66, CF-HAc1-UiO-66-NH2, and CF-HAc2-UiO-66-NH2, respectively, and the formic acid regulated as CF-FA-UiO-66 and CF-FA-UiO-66-NH2. The fabricated carboxylic acid modulated MOF fabric composites were well characterized using SEM, TGA, XRD, FTIR, and XPS spectra. The adsorption experiment results show that carboxylic acid modulated Zr based MOF fabric composites can serve as adsorbent for effective removal of Cr(VI) from water, in which the CF-FA-UiO-66-NH2 was prepared under the ratio of ZrCl4 and BDC-NH2 is 1.006 and with 5.47 M formic acid regulator exhibits that the optimal adsorption efficiency and the removal efficiency is 79.5 %. In addition, the adsorption of Cr(VI) in water by CFA-UiO-66-NH2 showed a quasi-secondary kinetic model following the Langmuir adsorption model, showing a a typical of chemisorption. What's more, the Cr(VI) removal efficiency and saturated adsorption capacity of CF-FA-UiO-66-NH2 was up to 80 % and 318.85 mg/g, respectively. The prepared CF-FA-UiO-66-NH2 MOF fabric composite was recyclable for removal of Cr(VI), and could be used as the potential adsorbent membrane for waste water treatment.